Pengaruh Aromaterapi Lavender dan Serai Merah Terhadap Penurunan Intensitas Nyeri Persalinan Kala I Fase Aktif Pada Ibu Primipara - Istiqomah, Amalia; Erisna, Maya; Wahyuni M., Sri; Astuti, Endri (Jurnal Kesehatan, 2022)
Pain in the active phase of labor will be felt heavier, sharper, and crampy and result in the spread of pain sensations. Pain and stress during labor can trigger the release of the hormone adrenaline. This hormone can cause the oxygen supply to the fetus to decrease, weaken uterine contractions to prolong the labor process. Prolonged labor pain can cause prolonged labor. The purpose of this study was to determine the differences in the effectiveness of lavender and red lemongrass aromatherapy in reducing pain intensity during the active phase in primiparous mothers. This research is quasi-experimental using pre and post-design without a control group. The study population was primiparous mothers who gave birth at the Brati Health Center and met the inclusion criteria. The sampling technique was non-probability sampling using a simple random sampling method. The study showed that the average pain intensity before giving lavender aromatherapy was 5.14 from 8, while the average labor pain intensity in the red lemongrass group before the intervention was 6.14 from 7.86. This indicates that lavender aromatherapy is more effective. when compared with the decrease in the intensity of physiological pain in primiparas by obtaining data for a mean rank of 19.25. In the red lemongrass group, the mean rank was 9.75. With a p-value of 0.001 (<0.05). From the results of the study, it is hoped that lavender aromatherapy and lemongrass aromatherapy can be applied in health care settings as a therapy to reduce pain intensity during labor.